Prevalence and epitope specificity of non-neutralising antibodies in a large cohort of haemophilia A patients without inhibitors - Lebreton, Aurélien; Lapalud, Priscilla; Chambost, Hervé; Biron-Andreani, Christine; Morange, Pierre-Emmanuel; Combescure, Christophe; Marques-Verdier, Alain; Berger, Claire; Schved, Jean-François; Granier, Claude; Lavigne-Lissalde, Géraldine (Thrombosis and Haemostasis, 2011)
Antibodies (inhibitors and non-neutralising antibodies [NNA]) directed against factor VIII (FVIII) remain the main iatrogenic complication in haemophilia A (HA) patients. Inhibitors reduce FVIII procoagulant properties, whereas NNA are directed against non-functional epitopes. NNA are poorly studied and their prevalence, epitope specificity and physiopathology inadequately defined. The aim of this study was first to evaluate NNA prevalence in a French retrospective multicentric series of 210 patients without inhibitors, then to determine their epitope specificity (against the heavy chain [HC] or the light chain [LC] of FVIII) and particularly to assess the prevalence of anti-B domain NNA using specifically designed x-MAP assays. NNA occurred in 18.1% of patients (38/210) and their prevalence was not influenced by the severity of the disease. Among the 38 patients with NNA, 73.7% had anti-FVIII Abs against the HC, 13.2% against the LC and 13.2% had anti-FVIII Abs against both chains. There is thus a clear immuno-dominance of the HC of FVIII in the epitope profile of NNA, whatever the severity of HA. The proportion of NNA that recognised the B domain was 18.4% (n=7/38). A multivariate analysis did not highlight differences in NNA occurrence between patients treated with recombinant FVIII or with plasma-derived FVIII (19.6% vs. 14.9%, p=0.53).
Keywords: Haemophilia A; factor VIII; x-MAP technology; non-neutralising antibodies; epitope mapping